Question Number 216010 by MATHEMATICSAM last updated on 25/Jan/25 | ||
![]() | ||
$$\mathrm{Solve}\:\mathrm{for}\:{x}\:\mathrm{and}\:{y} \\ $$$${ax}^{\mathrm{2}} \:+\:{bxy}\:+\:{cy}^{\mathrm{2}} \:=\:{bx}^{\mathrm{2}} \:+\:{cxy}\:+\:{ay}^{\mathrm{2}} \:=\:{d}. \\ $$ | ||
Answered by mr W last updated on 26/Jan/25 | ||
![]() | ||
$${ax}^{\mathrm{2}} +{bxy}+{cy}^{\mathrm{2}} ={d}\:\:\:...\left({i}\right) \\ $$$${bx}^{\mathrm{2}} +{cxy}+{ay}^{\mathrm{2}} ={d}\:\:\:...\left({ii}\right) \\ $$$$\left({i}\right)−\left({ii}\right): \\ $$$$\left({a}−{b}\right){x}^{\mathrm{2}} +\left({b}−{c}\right){xy}+\left({c}−{a}\right){y}^{\mathrm{2}} =\mathrm{0} \\ $$$$\left({a}−{b}\right)+\left({b}−{c}\right)\left(\frac{{y}}{{x}}\right)+\left({c}−{a}\right)\left(\frac{{y}}{{x}}\right)^{\mathrm{2}} =\mathrm{0} \\ $$$$\Rightarrow\frac{{y}}{{x}}={k}=\frac{{c}−{b}\pm\sqrt{\left({c}−{b}\right)^{\mathrm{2}} −\mathrm{4}\left({c}−{a}\right)\left({a}−{b}\right)}}{\mathrm{2}\left({c}−{a}\right)} \\ $$$$\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:=\frac{{c}−{b}\pm\left({b}+{c}−\mathrm{2}{a}\right)}{\mathrm{2}\left({c}−{a}\right)}=\begin{cases}{\mathrm{1}}\\{\frac{{a}−{b}}{{c}−{a}}}\end{cases} \\ $$$${from}\:\left({i}\right): \\ $$$${ax}^{\mathrm{2}} +{bkx}^{\mathrm{2}} +{ck}^{\mathrm{2}} {x}^{\mathrm{2}} ={d} \\ $$$$\left({a}+{bk}+{ck}^{\mathrm{2}} \right){x}^{\mathrm{2}} ={d} \\ $$$$\Rightarrow{x}=\pm\sqrt{\frac{{d}}{{a}+{bk}+{ck}^{\mathrm{2}} }} \\ $$$$\Rightarrow{y}=\pm{k}\sqrt{\frac{{d}}{{a}+{bk}+{ck}^{\mathrm{2}} }} \\ $$ | ||
Answered by Rasheed.Sindhi last updated on 26/Jan/25 | ||
![]() | ||
$${ax}^{\mathrm{2}} +{bxy}+{cy}^{\mathrm{2}} ={d}...\left({i}\right) \\ $$$${bx}^{\mathrm{2}} +{cxy}+{ay}^{\mathrm{2}} ={d}...\left({ii}\right) \\ $$$$\left({i}\right)−\left({ii}\right): \\ $$$$\left({a}−{b}\right){x}^{\mathrm{2}} +\left({b}−{c}\right){xy}+\left({c}−{a}\right){y}^{\mathrm{2}} =\mathrm{0} \\ $$$${factors}: \\ $$$$\left({a}−{b}\right){x}^{\mathrm{2}} −\left({a}−{b}\right){xy}−\left({c}−{a}\right){xy}+\left({c}−{a}\right){y}^{\mathrm{2}} =\mathrm{0} \\ $$$$\left({a}−{b}\right){x}\left({x}−{y}\right)−\left({c}−{a}\right){y}\left({x}−{y}\right)=\mathrm{0} \\ $$$$\left({x}−{y}\right)\left(\left({a}−{b}\right){x}−\left({c}−{a}\right){y}\right)=\mathrm{0} \\ $$$${x}−{y}=\mathrm{0}\:\mid\:\left({a}−{b}\right){x}−\left({c}−{a}\right){y}=\mathrm{0} \\ $$$$\begin{array}{|c|}{{x}={y}\:\mid\:{x}=\frac{\left({c}−{a}\right){y}}{{a}−{b}}}\\\hline\end{array} \\ $$$${x}={y} \\ $$$$\:\left({i}\right)\Rightarrow{ax}^{\mathrm{2}} +{bx}^{\mathrm{2}} +{cx}^{\mathrm{2}} ={d} \\ $$$$\:\:\:\:\:\:\:\Rightarrow{x}={y}=\pm\sqrt{\frac{{d}}{{a}+{b}+{c}}}\:\:\:\checkmark \\ $$$$\: \\ $$$${x}=\frac{\left({c}−{a}\right){y}}{{a}−{b}}\:: \\ $$$${a}\left(\frac{\left({c}−{a}\right){y}}{{a}−{b}}\right)^{\mathrm{2}} +{b}\left(\frac{\left({c}−{a}\right){y}}{{a}−{b}}\right){y}+{cy}^{\mathrm{2}} ={d} \\ $$$${y}^{\mathrm{2}} \left(\frac{{a}\left({c}−{a}\right)^{\mathrm{2}} +{b}\left({a}−{b}\right)\left({c}−{a}\right)+{c}\left({a}−{b}\right)^{\mathrm{2}} }{\left({a}−{b}\right)^{\mathrm{2}} }\right)={d} \\ $$$${y}^{\mathrm{2}} =\frac{{d}\left({a}−{b}\right)^{\mathrm{2}} }{{a}\left({c}−{a}\right)^{\mathrm{2}} +{b}\left({a}−{b}\right)\left({c}−{a}\right)+{c}\left({a}−{b}\right)^{\mathrm{2}} } \\ $$$$\: \\ $$$${y}=\pm\left({a}−{b}\right)\sqrt{\frac{{d}}{{a}\left({c}−{a}\right)^{\mathrm{2}} +{b}\left({a}−{b}\right)\left({c}−{a}\right)+{c}\left({a}−{b}\right)^{\mathrm{2}} }} \\ $$$$\: \\ $$$${y}=\pm\left({a}−{b}\right)\sqrt{\frac{{d}}{{a}^{\mathrm{3}} +{ab}\left({b}−{a}\right)+{ac}\left({c}−{a}\right)−{abc}}} \\ $$$${x}=\pm\frac{\left({c}−{a}\right)}{{a}−{b}}\left\{\left({a}−{b}\right)\sqrt{\frac{{d}}{{a}^{\mathrm{3}} +{ab}\left({b}−{a}\right)+{ac}\left({c}−{a}\right)−{abc}}}\:\right\} \\ $$$$\begin{cases}{{x}=\pm\left({c}−{a}\right)\sqrt{\frac{{d}}{{a}^{\mathrm{3}} +{ab}\left({b}−{a}\right)+{ac}\left({c}−{a}\right)−{abc}}}}\\{{y}=\pm\left({a}−{b}\right)\sqrt{\frac{{d}}{{a}^{\mathrm{3}} +{ab}\left({b}−{a}\right)+{ac}\left({c}−{a}\right)−{abc}}}\:\:}\end{cases}\:\checkmark \\ $$ | ||